Pengaruh Jantung Pisang (Musa Paradisiaca L.) terhadap Produksi ASI - Wulan, Sri; Br. Girsang, Desri Meriahta (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
The World Health Organization recommends that every baby be exclusive breastfeeding until the baby reaches the first 6 months of age, because breastfeeding is an important part of the baby's diet until the baby is six month to two years old and the mother is the main source of milk production so that the mother's nutrition must be fulfilled. This study aims to determine the effect of banana blossoms on milk production. The method used the Quasi Experiment with a Pretest-Posttest With Control Group design. The population in this study were all mothers breastfeeding infants aged 0-6 months in Sidodadi Ramunia Village, Beringin District Sampling using Probability Sampling technique by determining the inclusion and exclusion criteria of 20 breastfeeding mothers. Data analysis using frequency distribution data and Independent Sample Test with a confidence level of 95%. The results showed that the smoothness of breastfeeding in the intervention group and the control group, there was a difference in value of 149.0 with a p value of 0.01, which means that there was a significant difference in the two groups and seen from the infant indicator, the difference in the average value of urine elimination for infants in the intervention and control groups was 24.00 with p 0.001, the difference in the average value of the frequency of baby defecation is 0.900 with a p value of 0.027 and seen from the number of hours of sleep for babies there is a difference in the value of 3.100 with a p value of 0.025 which means that there is an effect of giving banana blossoms stew on milk production, both seen from the smoothness of the mother's milk or from the baby indicator. It is recommended for nursing mothers to routinely consume banana blossoms because banana blossoms are proven to increase milk production.